Computers and the Gender Wage Differential - Wong, Linda Yuet-Yee (Journal of Income Distribution®, 2008)
In this article, I report results of an exploratory data analysis that challenge the conventional wisdom on the relation between computer use and gender wage. Using the micro-economic data of 1984, 1993, and 2001, I find 1) the wage premium for females using computers at work is about 19-26 per cent higher than males within the high bluecollar sector, and 2) college-educated females who use computers at work earn a substantially higher wage than college-educated males. These results indicate that computers have re-structured work by deemphasizing physical skill that benefits women, and that college- educated women in the white-collar sector have unobserved female labor quality that could positively correlate with computer skill.